How to dismantle an atomic bomb [compact disc] / U2. - Edge (Musician), 1961-; Clayton, Adam; Mullen, Larry; Bono, 1960- (Interscope Records, 2004)
Making another run for Number One, the political Irish rockers follow up 2000's Grammy-winning ALL THAT YOU CAN'T LEAVE BEHIND with a return to raw, expansive guitar-work and soaring choruses. "Vertigo" is the lead single.